2025 SFP Prioritization Tool Prototype - Youngberg, Brayden; Ghosh, Aniruddha; Steward, Peter Richard; Rosenstock, Todd Stuart; Schmitter, Petra (2025)
This repository contains initial explorations and prototyping to support early discussions for CGIAR Sustainable Farming Program prioritization. It is the result of brainstorming and testing to refine variable selection, weighting, and aggregation for country-level prioritization. As a prototype, it is focused on experimentation rather than informing finalized decisions, and it can be easily modified to include different indicators, methods, etc.